Construction and Analysis of Plastic Extruder Machine for Polyethylene Plastic Waste - Muhammad Luthfi Sonjaya; Muh Farid Hidayat (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
Polyethylene plastic waste is such hazard object in the world, while the benefits of this plastic rubbish are prodigious. An extruder machine is one of the great ways to reduce huge amounts of plastic waste not only to the manufacturing companies which recycle the plastic waste but also to the small society. This extruder machine was created to overcome the problems faced by all countries about plastic waste in land or in ocean. The results of extruded plastic waste were solid filament that can be utilized for some valuable stuff made by plastic. From this study, experimental test was applied by heating the plastic waste with different temperatures of 150, 160, 170, 180, 190, 200, 210, 220, and 230°C. As a result, the best temperature to heat the polyethylene plastic waste is 190°C according to surface roughness test and digital caliper measurement.